Seni Prasi Dalam Kajian Antopologi Dan Sosiologi - Lodra, I Nyoman (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Pracy Art is a kind of painting using leaf lontar media which is painted with the sharp iron, the formercharcoal mixed with coconut oil slightlyy on its surface. Themes are revealed; Mahabrata, Ramayana, Sotasoma,Tantri, and other folklore. The existence of the palm leaf is important in the life of the people of Geriya, Talibeng,Sidemen, Karangasem. Because the art is part of the civilization of Ancient Bali. To understand more deeply aboutthis art of pracy it is necessary to approach with anthropology and Sociology. Both fields of science are related to humanlife in the activity of art. This Study the focuses on the discussion in